2021
DOI: 10.1016/j.jcot.2020.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Operative versus conservative treatment of proximal rectus femoris avulsions: A systematic review with meta-analysis of clinical outcomes, complications and return to sports

Abstract: Prospero registration number: CRD42020198333. Objective: To compare the surgical and conservative treatment of proximal rectus femoris avulsions regarding clinical outcomes, rate of return to sports and incidence of complications. Design: Systematic review and meta-analysis. Data sources: Cochrane, Medline, Scopus and SPORTDiscus. Eligibility criteria for selecting studies: Studies reporting on outcomes of PRFAs or return to sports were included.Results: Nine studies consisting of a total eighty-two patients m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
1
4
0
2
Order By: Relevance
“…Timing of RTP for athletes undergoing operative management was 22.1 weeks, compared with 11.7 weeks for athletes treated nonoperatively. This finding corresponds with the results reported by Dalal et al 6 in their analysis of 9 studies (N = 82 patients), observing that athletes who underwent nonoperative management returned at a faster rate (69.2 days) compared with athletes who underwent operative management (112.6 days). Furthermore, the authors reported a RTP rate of 95% in the operative group versus 92.7% in the conservative treatment group ( P = .93).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Timing of RTP for athletes undergoing operative management was 22.1 weeks, compared with 11.7 weeks for athletes treated nonoperatively. This finding corresponds with the results reported by Dalal et al 6 in their analysis of 9 studies (N = 82 patients), observing that athletes who underwent nonoperative management returned at a faster rate (69.2 days) compared with athletes who underwent operative management (112.6 days). Furthermore, the authors reported a RTP rate of 95% in the operative group versus 92.7% in the conservative treatment group ( P = .93).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the authors reported a RTP rate of 95% in the operative group versus 92.7% in the conservative treatment group ( P = .93). 6 Our review of the literature found a 100% RTP rate in athletes treated operatively compared with 93.3% of athletes treated nonoperatively. Athletes undergoing operative treatment had a higher RTP rate but longer convalescence compared with those athletes managed nonoperatively.…”
Section: Discussionmentioning
confidence: 82%
“…A recent meta-analysis by Dalal et al [ 9 ] on conservative vs. operative treatments of PRFA injuries found similar results between the groups with a slightly higher return to sport rate for the surgically treated group (95%) compared to the conservatively treated group (92.7%), without statistical significance ( p = 0.93). In addition, an earlier return to sport was observed for injuries that underwent surgery immediately vs. injuries that underwent surgery after failed initial conservative treatment (112.6 days vs. 204.6 days).…”
Section: Discussionmentioning
confidence: 88%
“…Within quadriceps injuries, the rectus femoris (RF) muscle is known to be the most commonly affected muscle [ 8 , 29 ]. Proximal RF injuries mainly occur during sprints and kicking movements [ 19 ], and present as myofascial injuries, small to complete ruptures at the myotendinous junction, midsubstance ruptures, or avulsion injuries from its anatomic origin [ 4 , 9 , 15 , 19 , 21 23 , 25 , 26 , 33 ]. For proximal rectus femoris avulsions (PRFA), operative treatment options include suture anchor repair and tenodesis with excision of the proximal tendon in which both alternatives yield satisfactory results primarily in small case series [ 23 , 26 , 28 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Die Rückkehr zum Sport ist nach einer konservativen Therapie in den meisten Fällen möglich, jedoch sind Heilungsverläufe von 6 bis 12 Monaten keine Seltenheit [11,20,21]. Laut einer Übersichtsarbeit von Dalal et al [22] sind persistierende Hüftschmerzen [16] unter höherer Trainingsbelastung mit Kraftdefiziten in der Hüftflexion vor allem auf Hochleistungssportniveau [23] häufige Komplikationen und bedürfen im weiteren Verlauf einer operativen Refixation. Auch Rerupturen sind nach einer nicht operativen Therapie der RF-Ruptur mit 18% [24] noch immer sehr hoch und sollten in der Behandlung und im Umgang mit Athleten berücksichtigt werden.…”
Section: Therapieunclassified